The political economy of technological change, energy and climate change - Howarth, N; Nicholas Howarth (2012)
This thesis sets out to explore some of the key dimensions in the process of socio-technological change inherent in the shift to a low carbon economy. This is done in two parts, the first focusing on theory, the second, empirical case studies. Out of the diversity of interactions between actors, technologies, and policies surrounding this process, one key question emerges: can societies really shift the structure of their economies so fundamentally to achieve a low carbon future within a reasonable timeframe? Chapter One develops an integrated approach to economic and political change to interrogate this question. This synthesizes a review of literature (Part One) examining the role of technology within some of the main theories of economic change in the social sciences. Two broad paradigms are distinguished. First, a paradigm based around the notion of equilibrium, notably the standard welfare approach of neoclassical economics; and secondly, an evolutionary paradigm, which views the economy as a complex adaptive system – such as exemplified by theories of path dependency. This theoretical background provides a broad narrative to frame and inform Part Two of the thesis. First in Chapter Four, socio-technical change is investigated in the context of the diffusion of energy efficient lighting in Germany. This study investigates the relationships between human behaviour and attitudes, lamp technology and the evolving nature of institutions, to provide a framework with which to consider the contentious issue of individual freedom versus government control in the politics of change to lower-carbon emissions. In Chapter Five, the case for the creation of a market for CO2 pollution permits is developed. In making this case, the strengths and weaknesses of emissions trading are compared and contrasted with other policy instruments and the broader political economy of the various policy options discussed. Chapter 6 builds on this to examine the political economy of implementing an emissions trading scheme in Australia and the impact the Kyoto Protocol has had on domestic politics and GHG mitigation. Chapter Seven continues with the theme of building ‘a political ecology of the state’ by investigating the politics and economics of greenhouse gas mitigation in Russia. Finally, Chapter Eight recapitulates the aims, nature and conclusions of this research and draws out its implications for policy as well as mapping out some areas for further research. In particular, the need to bring a greater sense of politics back into the study of the economy is highlighted as a vital part of building a renewed, more sustainable economic paradigm in the wake of the financial crisis and, as a way of strengthening the connection between social values and market outcomes.